EFFECT OF REPLACING SOYBEAN MEAL WITH LARVAE MEAL OF BLACK SOLDIER FLY HERMETIA ILLUCENS IN GROWTH PERFORMANCE AND SOME BIOCHEMICAL BLOOD PARAMETERS OF COMMON CARP CYPRINUS CARPIO L. - Ahmed I. Albayati; R. S. Attee; M. S. Al-Khshali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted at the College of Agriculture/ Diyala University/ Department of Animal production to determine the effect of replacing soybean meal with black soldier fly Hermetia illucens larvae meal on the growth performance and some biochemical blood parameters of common carp Cyprinus carpio L. One hundred and five fish with an average initial weight of 27.46±0.14 g was used in this experiment. They were randomly distributed into five treatments (3 replicate/treatment, 7 fish/ replicate). The first treatments (T1 control group) was fed with standard diet without black soldier fly larvae meal (0% BSFLM), black soldier fly larvae meal were substituted for soybean meal in other experimental groups at 25%, 50%, 75% and 100% (T2, T3, T4 and T5), respectively. After 12 weeks of feeding, no significant differences (P>0.05) were found in feed conversion ratio (FCR) and protein efficiency ratio (PER) between control and experimental groups. However, T4 (75% BSFLM) showed significantly improved in mean of final body weight (FBW) and weight gain (WG) compared to the control and other experimental groups. The results of serum biochemical indices showed no statistically significant differences (P>0.05) in the levels of ALT (Alanine aminotransferase), Glucose, Triglycerides, LDL (low-density lipoprotein) and total protein (TP) between control and experimental groups. While AST (Aspartate aminotransferase) level of T4 and T5 was significantly higher (P≤0.05) than T3. As a result, the study suggests that black soldier fly larval meal can be a sustainable protein alternative to soybean meal at 75% without affecting growth performance or blood biochemical characteristics.